Il Corporativismo nell'Italia di Mussolini Dal declino delle istituzioni liberali alla Costituzione repubblicana - Barucci, Piero; Bini, Piero; Conigliello, Lucilla (Studi e saggi, 2018)
This volume collects ten essays on the expansion of the public government of economy during Fascist corporatism. Some of the texts deal with the problematic relationship between intellectuals (such as Luigi Einaudi, Attilio Cabiati, Ugo Spirito, Nino Massimo Fovel) and Mussolini's dictatorship. Other essays discuss with a critical eye the fiscal policy choices of the period and the different aspects related to the public finance reform. Some authors then investigate the relationship between administrative law and corporate law, offering a precise commentary of the two 1939 Italian laws on the protection of the landscape and artistic heritage. The volume on the interchange between Italian and German economic thought from 1918 to 1945 occupies a relevant place within the main volume, and so does the one written by Sabino Cassese: the author, starting from his several studies, reflects on the general sense of the historical event of Fascism.